Mitigasi Berbasis Komunitas: Pelatihan dan Simulasi Penanggulangan Bencana di Desa Barakati - Citron S. Payu; Dewa Gede Eka Setiawan; I Made Hermanto (Universitas Negeri Gorontalo, 2026)
Barakati Village in Batudaa District, Gorontalo Regency, is highly vulnerable to floods and landslides. This community service program aims to improve disaster literacy, strengthen community participation, and establish a local mitigation system. Activities included training, evacuation drills, preparation of SOPs and evacuation maps, as well as environmental cleanup and tree planting. The outcomes of this program include increasing community awareness and involvement, establishing a Disaster Resilient Village volunteer group (Destana), and providing practical benefits for both villagers and students.